EffectofcorpusluteumirrigationassessedbyDopplerultrasoundonthegestationpercentageofembryo recipientHolsteincows - Alvarado, D.; Narváez, H. J.; Fazan-Rossi, G. [UNESP]; Mansano-Garcia, J. [UNESP] (My University, 2022)
The luteal vasculature plays a critical role in corpus luteum (CL) function and provides important information on the physiology and pathophysiology of this structure. To quantify the blood flow of the luteal tissue, Doppler ultrasound is used to detect the flow of red blood cells through the blood vessels. The objective of the present study was to determine the degree of irrigation of the CL evaluated by Doppler ultrasound on the day (D0) of embryo transfer (ET) and 25 days post-transfer and its relationship with the percentage of early gestation in Holstein recipient cows. Thirty multiparous, non-lactating Holstein cows were used as in vitro embryo recipients. The blood supply rate of the CL and the percentage of gestation were evaluated. The corpora lutea were categorized into 1 (high), 2 (medium) and 3 (low) according to the degree of blood supply. The percentage of cows with these degrees of CL irrigation on the day of transfer were 50% (15/30), 23.3% (7/30) and 27.7% (8/30). On day 25 post-transfer they were 33.3% (10/30), 43.3% (13/30) and 23.3% (7/30), respectively. Additionally, the percentage of early gestation (25 days post-transfer) was evaluated for grades 1, 2 and 3 of CL blood supply, whose results were: 20% (6/30), 6.6% (2/30) and 0%, respectively. It was possible to conclude that the Holstein breed recipients classified in high degree of CL blood irrigation, presented better (P < 0.05) percentage of gestation of embryos of in vitro origin.
Efecto de la irrigación del cuerpo lúteo evaluado mediante ecografía Doppler sobre el porcentaje de gestación de vacas Holstein receptoras de embriones
Keywords: Bos taurus; corpus luteum; Doppler ultrasound; embryo transfer; pregnancy rates